What is being a teacher in the countryside? Conceptions of Brazilian peasant higher education students about the Supervised Curricular Internship - Gustavo Cunha de Araujo; Helena Quirino Porto Aires (Acta Scientiarum. Human and Social Sciences, 2018)
The present paper has the objective of analyzing students' conceptions about the supervised curricular internship in the Licentiate degree in Rural Education with qualification in Arts and Music, at the Federal University of Tocantins, Campus Tocantinópolis, Brazil. We also propose with this text to address the historical and pedagogical aspects of this course, as well as to discuss the importance of the Internship for the educators’ training of to work in countryside schools. This case study was based on the qualitative approach, with documentary research and semi structured interviews with students of this course as data collection instruments. The type of data analysis - theoretical and empirical - followed the perspective of the interpretative research technique. The results demonstrated that in order to overcome the challenges faced by students and teachers of the Licentiate degree in Rural Education with qualification in Arts and Music of UFT in Tocantinópolis, demands elaborating a proposal of joint training between the training institutions and the school, in the sense to guarantee actions that will attend the various subjects, especially those of the Rural Education.